Performance Analysis Of Data Transmission Via Power Line Carrier Communication System - Adha Yusoff, Intan (Universiti Sains Malaysia, 2006)
Power Line Carrier Communication System is a new technology in communication. The idea has been around for years, but the implementation is a highly difficult task. The service associated the power signals to be the carrier for data signals, and using the power line to reach its destination. In data transmission the two nodes need to be in phase and simultaneous with each other to protect data signals from being lost. In data transmission, high performance network is needed because of the high frequency of data signals, whereas in power line there are high currents. The throughput data for PLC system and CAT5 cable network system will later be collected and analyzed to see how far is the PLC performance compared to the now available technology. Besides the comparisons, this project will also study the atand alone performance of in-house PLC using reliable softwares such as PCATTCP, and other network monitoring programs. In-house PLC products can support services where it is possible for simple data transmission networking, and the no new wiring characteristics of this technology can be seen.